ELIGULUM-A Regulates Lateral Branch and Leaf Development in Barley. Issue 4 (12th February 2018) - Okagaki, Ron J.; Haaning, Allison; Bilgic, Hatice; Heinen, Shane; Druka, Arnis; Bayer, Micha; Waugh, Robbie; Muehlbauer, Gary J.
Abstract : The barley ELIGULUM-A gene regulates lateral branch development and acts to establish the blade-sheath boundary during leaf development. Abstract: The shoot apical and axillary meristems control shoot development, effectively influencing lateral branch and leaf formation. The barley ( Hordeum vulgare ) uniculm2 ( cul2 ) mutation blocks axillary meristem development, and mutant plants lack lateral branches (tillers) that normally develop from the crown. A genetic screen for cul2 suppressors recovered two recessive alleles of ELIGULUM-A ( ELI-A ) that partially rescued the cul2 tillering phenotype. Mutations in ELI-A produce shorter plants with fewer tillers and disrupt the leaf blade-sheath boundary, producing liguleless leaves and reduced secondary cell wall development in stems and leaves. ELI-A is predicted to encode an unannotated protein containing an RNaseH-like domain that is conserved in land plants. ELI-A transcripts accumulate at the preligule boundary, the developing ligule, leaf margins, cells destined to develop secondary cell walls, and cells surrounding leaf vascular bundles. Recent studies have identified regulatory similarities between boundary development in leaves and lateral organs. Interestingly, we observed ELI-A transcripts at the preligule boundary, suggesting that ELI-A contributes to boundary formation between the blade and sheath. However, we did not observe ELI-A transcripts at the axillary meristem boundary in leaf axils, suggesting that ELI-A is not involved in boundary development for axillary meristem development. Our results show that ELI-A contributes to leaf and lateral branch development by acting as a boundary gene during ligule development but not during lateral branch development.